Znaczenie Inicjatywy Pasa i Szlaku dla relacji bilateralnych Republiki Turcji oraz Chińskiej Republiki Ludowej .......... 85 - Sypień, Katarzyna (Oblicza dyplomacji, 2025)
THE SIGNIFICANCE OF THE BELT AND ROAD INITIATIVE FOR BILATERAL RELATIONSHIP BETWEEN TÜRKIYE AND THE PEOPLE’S REPUBLIC OF CHINAAnnounced in 2013 by Xi Jinping, President of the People’s Republic of China (PRC), the Belt and Road Initiative (BRI) projects the construction of trade routes to build new institutional links and investment networks and bring Asia, Europe, Africa and the Middle East closer together economically. The relationship between Türkiye and PRC is characterized by considerable fluctuation, but an increase in stability has been observable since the signing of the Strategic Partnership and the BRI Accession Agreement. This article examines the evolution of the BRI through various sectoral and non-economic initiatives and Chinese strategies towards Türkiye, the Turkish approach to the BRI and the relevance of the Belt and Road Initiative for Sino-Turkish bilateral relations.